2022
DOI: 10.1038/s41598-022-17885-7
|View full text |Cite|
|
Sign up to set email alerts
|

The use of interdental cleaning devices and periodontal disease contingent on the number of remaining teeth in Korean adults

Abstract: This study aimed to investigate the effect of interdental brushes and dental floss on the prevention of periodontitis in participants with ≥ 20 or < 20 remaining teeth by using the Korea National Health and Nutrition Examination Survey 2016–2018. Data from 11,614 participants were analysed using multivariate logistic regression after adjusting for sociodemographic factors (age and sex), socioeconomic factors (level of education and individual income), oral health-related variables (daily toothbrushing), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…34 As previous studies have indicated the need to divide into those with 20 or more remaining teeth and those with fewer than 20 remaining teeth to accurately assess the effects of interdental cleaning devices among in older people, we conducted our analysis in these two groups. 35 In this study, there were more participants with 20 or more teeth than those with 20 or fewer teeth. Furthermore, the effective of dental floss is higher in the group with 20 or more teeth.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 80%
See 1 more Smart Citation
“…34 As previous studies have indicated the need to divide into those with 20 or more remaining teeth and those with fewer than 20 remaining teeth to accurately assess the effects of interdental cleaning devices among in older people, we conducted our analysis in these two groups. 35 In this study, there were more participants with 20 or more teeth than those with 20 or fewer teeth. Furthermore, the effective of dental floss is higher in the group with 20 or more teeth.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 80%
“…The reason for this is likely that dental literacy and knowledge are disseminated more through the media, and thus the significance of oral health is conveyed accordingly 34 . As previous studies have indicated the need to divide into those with 20 or more remaining teeth and those with fewer than 20 remaining teeth to accurately assess the effects of interdental cleaning devices among in older people, we conducted our analysis in these two groups 35 . In this study, there were more participants with 20 or more teeth than those with 20 or fewer teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into two groups based on the number of remaining teeth (≥20, <20) according to previously described reports. 33,34 Patient demographic and clinical characteristics were compared between groups, and mean values, standard deviations, medians, 25-75 percentiles, and p-values were calculated. We used the χ 2 -test or Fisher's exact test for categorical values, and used Student's t test or the Mann-Whitney U test for continuous values.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into two groups based on the number of remaining teeth (≥20, <20) according to previously described reports 33,34 . Patient demographic and clinical characteristics were compared between groups, and mean values, standard deviations, medians, 25–75 percentiles, and p ‐values were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to randomized clinical trials, cross‐sectional (Cepeda et al, 2017; Kim & Han, 2021; S. J. Kim, Lee, et al, 2022; Y. J. Kim, Gil, et al, 2022; Lang et al, 1995; Lee et al, 2018; Marchesan et al, 2018) and cohort studies (Chaffee et al, 2020; Kressin et al, 2003; Marchesan et al, 2020) predominantly reported that both flossing and interdental brushing in addition to toothbrushing were associated with lower levels of periodontitis, caries and tooth loss among different populations with a predominantly wide age range (19+/30+ years). In three repeated cross‐sectional studies, IDA use explained a significant portion of explainable changes in the mean probing depth (PD), the number of caries‐free healthy surfaces and the number of teeth (Pitchika et al, 2021).…”
Section: Introductionmentioning
confidence: 99%